Magnetically separable reduced graphene oxide/iron oxide nanocomposite materials for environmental remediation - Teo, Peik See; Pandikumar, Alagarsamy; Lim, Hong Ngee; Huang, Nay Ming; Chia, Chin Hua (Royal Society of Chemistry, 2014)
Magnetically separable reduced graphene oxide/iron oxide (rGO/Fe3O4) nanocomposite materials were synthesized at room temperature through a facile, eco-friendly and cost-effective approach. The prepared nanocomposite materials were characterized by different techniques. X-ray diffraction analysis revealed the formation of the rGO/Fe3O4 nanocomposites, while transmission electron microscope images showed that the Fe3O4 nanoparticles with an average size of 10 nm were embedded uniformly on the surface of rGO sheets. The synthesized rGO/Fe3O4 nanocomposite materials were found to be super-paramagnetic in nature at room temperature. The photocatalytic performance of the rGO/Fe3O4 nanocomposite materials was investigated under natural sunlight irradiation using methylene blue (MB) as a model target organic pollutant. The rGO/Fe3O4 showed better adsorption behaviour and excellent photocatalytic activity towards the degradation of MB, when compared to other samples such as rGO and pristine Fe3O4 nanoparticles. This enhanced photocatalytic activity could be attributed to the synergistic effect that arises between the rGO and Fe3O4, which significantly reduces charge recombination. Moreover, the rGO/Fe3O4 nanocomposite materials exhibited good sustainability, which was evidenced by their consistent photocatalytic performance and the absence of any observable changes in morphology, even after eight cycles of operation during photocatalytic experiments. The overall results of the study indicate that these newly prepared photocatalytically stable and magnetically separable rGO/Fe3O4 nanocomposites could be potentially utilized for many environmental remediation applications.